2021
DOI: 10.1021/acsomega.1c01642
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Biopolymer Architecture Enhanced the Adsorption and Selectivity of Aqueous Heavy-Metal Ions

Abstract: Halloysite nanotubes (HNT) and ball-milled biochar (BC) incorporated biocompatible mesoporous adsorbents (HNT-BC@Alg) were synthesized for adsorption of aqueous heavy-metal ions. HNT-BC@Alg outperformed the BC, HNT, and BC@Alg in removing cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb). Mesoporous structure (∼7.19 to 7.56 nm) of HNT-BC@Alg was developed containing an abundance of functional groups induced from encapsulated BC and tubular HNT, which allowed heavy metals to infiltrate and interact with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…According to the United States Environmental Protection Agency, the permissible total amounts of Cr and Pb in drinking water is below 0.1 and 0.015 mg L –1 , respectively . Therefore, different technologies have been proposed for the decontamination of these pollutants including membrane separation, chemical precipitation, biodegradation, photodegradation, and adsorption. , Among these methods, adsorption is recognized as one of the most promising approaches owing to its low cost, simple implementation, and the absence of secondary pollutants . It has been reported that the cost of water treatment with nonadsorption technologies is in the range of 10 to 450 USD/m 3 of purified water, whereas adsorption-based approaches range from 5 to 200 USD/m 3 with approximately 70% of the cost related to the production of the adsorbent material .…”
Section: Introductionmentioning
confidence: 99%
“…According to the United States Environmental Protection Agency, the permissible total amounts of Cr and Pb in drinking water is below 0.1 and 0.015 mg L –1 , respectively . Therefore, different technologies have been proposed for the decontamination of these pollutants including membrane separation, chemical precipitation, biodegradation, photodegradation, and adsorption. , Among these methods, adsorption is recognized as one of the most promising approaches owing to its low cost, simple implementation, and the absence of secondary pollutants . It has been reported that the cost of water treatment with nonadsorption technologies is in the range of 10 to 450 USD/m 3 of purified water, whereas adsorption-based approaches range from 5 to 200 USD/m 3 with approximately 70% of the cost related to the production of the adsorbent material .…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane bagasse based adsorption removal shows selectivity based on physicochemical properties of HMs (Homagai et al 2010;Saxena et al 2017;Hassan et al 2021;Mondal et al 2022). Also, the literature shows that SCB adsorption removal of different heavy metals under similar experimental setups, shows different adsorption capacity (Kong et al 2014;Tran et al 2017;Ighalo et al 2022).…”
Section: Heavy Metals Bio-adsorption Removal Potentials Of Waste Bagassementioning
confidence: 99%
“…However, pseudo second order kinetics of initial rapid adsorption is due to the large binding sites of bagasse functional groups. In contrast, slow adsorption onto residual binding sites and diffusion of heavy metals into the porous surface follows pseudo first order kinetic models (Hassan et al 2021). Most adsorption kinetics of modified and unmodified SCB for metal ion removal have been reported as pseudo first and pseudo second order kinetic models (Irawan et al 2021;Iwuozor et al 2021a).…”
Section: Adsorption Kinetics Of Bagasse Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2). The presence of mesopores favors ions transportation to active sorption sites (Cuong et al 2019), increasing the effectiveness and speed of the sorption process (Hassan et al 2021). The surface area plays an important role in metal sorption since this is a surface phenomenon (Nascimento et al 2014) and can vary widely, even among close feedstocks.…”
Section: Characterization Of Biocharsmentioning
confidence: 99%